Novel Synthesis of Kanamycin Conjugated Gold Nanoparticles with Potent Antibacterial Activity - Payne, Jason N.; Waghwani, Hitesh K.; Connor, Michael G.; Hamilton, William; Tockstein, Sarah; Moolani, Harsh; Chavda, Fenil; Badwaik, Vivek; Lawrenz, Matthew B.; Dakshinamurthy, Rajalingam (Frontiers in Microbiology, 2016)
With a sharp increase in the cases of multi-drug resistant (MDR) bacteria all over the world, there is a huge demand to develop a new generation of antibiotic agents to fight against them. As an alternative to the traditional drug discovery route, we have designed an effective antibacterial agent by modifying an existing commercial antibiotic, kanamycin, conjugated on the surface of gold nanoparticles (AuNPs). In this study, we report a single-step synthesis of kanamycin-capped AuNPs (Kan-AuNPs) utilizing the combined reducing and capping properties of kanamycin. While Kan-AuNPs have increased toxicity to a primate cell line (Vero 76), antibacterial assays showed dose-dependent broad spectrum activity of Kan-AuNPs against both Gram-positive and Gram-negative bacteria including Kanamycin resistant bacteria. Further, a significant reduction in the minimum inhibitory concentration (MIC100) of Kan-AuNPs was observed when compared to free kanamycin against all the bacterial strains tested. Mechanistic studies using transmission electron microscopy and fluorescence microscopy indicated that at least part of Kan-AuNPs increased efficacy may be through disrupting the bacterial envelope, resulting in the leakage of cytoplasmic content and the death of bacterial cells. Results of this study provide critical information about a novel method for the development of antibiotic capped AuNPs as potent next-generation antibacterial agents.